Expression of Synthetic pac Gene Encoding Penicillin G Acylase (PGA) Enzyme in E. coli BL21(DE3) and HB101 - Amin, Achmad Makin; Sismindari, Sismindari; Purwanto, Purwanto (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2024)
High bacterial infection cases in Indonesia cause a high need for antibiotic drugs. Unfortunately, most of the raw materials used for antibiotic production in Indonesia are still imported. For this reason, the government is eager to find better ways to produce penicillin and its derivatives, which are widely used in society. The production of penicillin-derivative requires penicillin G acylase (PGA) as a catalyst. In previous studies, the expression of the syn-pac gene in E. coli BL21(DE3) to produce a recombinant PGA enzyme was performed, but the enzyme activity was low (0.01754 U/mg). Thus, the expression was carried out in different hosts and inducers. The purpose of this research was to obtain the production of PGA with higher enzyme activity. The transformation was carried out in the pET22b-pacEc in E. coli BL21(DE3) and HB101. For enzyme expression, the recombinant hosts were induced by 0.05 mM IPTG, 176 mM lactose, and 1998 mM arabinose at a temperature of 20°C and 150 rpm of shaking for 17 h. Protein isolation was performed by sonication and freeze-thawing to recover biologically active PGA. Verification of PGA was performed by SDS-PAGE and the enzyme activity was tested by pDAB. E. coli HB101 produced PGA with higher activity (10.17 U/mg) than BL21(DE3) (6.67 U/mg), and arabinose was the strongest inducer for enzyme expression.